Combined hepatocellular‐cholangiocarcinoma: A population‐level analysis of an uncommon primary liver tumor. Issue 8 (3rd July 2014) - Garancini, Mattia; Goffredo, Paolo; Pagni, Fabio; Romano, Fabrizio; Roman, Sanziana; Sosa, Julie Ann; Giardini, Vittorio
<x xml:space="preserve">Abstract</x> Combined hepatocellular‐cholangiocarcinoma (cHCC‐CC) is a rare primary liver cancer. Our aims were to analyze the demographic, clinical, and pathological characteristics of cHCC‐CC at a population level and to investigate the effects of these features as well as different management strategies on the prognosis. The Surveillance, Epidemiology, and End Results (SEER) database was analyzed for 1988‐2009. Data analyses were performed with chi‐square tests, analyses of variance, Kaplan‐Meier curves, and Cox proportional hazards regression. Four hundred sixty‐five patients with cHCC‐CC, 52, 825 patients with hepatocellular carcinoma (HCC), and 7181 patients with cholangiocarcinoma (CC) were identified. cHCC‐CC was more common in patients who were white, male, and older than 65 years. Treatment was more frequently nonsurgical/interventional. Patients with cHCC‐CC, HCC, and CC had 5‐year overall survival (OS) and disease‐specific survival rates of 10.5%, 11.7%, and 5.7% (P < 0.001) and 17.8%, 21.0%, and 11.9% (P < 0.001), respectively. For cHCC‐CC patients, an increasing invasiveness of the therapeutic approach was significantly associated with prolonged survival (P < 0.001). In a multivariate model, black race, a distant SEER stage, and a tumor size of 5.0 to 10.0 cm were independently associated with lower survival for cHCC‐CC patients; a year of diagnosis after 1995 and surgical treatment with minor hepatectomy, major hepatectomy (MJH), or liver transplantation (LT) were independently associated with better survival for cHCC‐CC patients. Patients diagnosed with cHCC‐CC, HCC, and CC and treated with LT had 5‐year OS rates of 41.1%, 67.0%, and 29.0%, respectively (P < 0.001). In conclusion, cHCC‐CC patients appear to have intermediate demographic, clinical, and survival characteristics in comparison with HCC and CC patients. cHCC‐CC patients undergoing LT showed inferior survival in comparison with HCC patients, and the role and indications for LT in cHCC‐CC have yet to be defined. At this time, MJH may be considered the best therapeutic approach for such patients. Liver Transpl 20:952–959, 2014. © 2014 AASLD.